Use of giant unilamellar lipid vesicles as antioxidant carriers in in vitro culture medium of bovine embryos - Rossi, Luana Teixeira Rodrigues [UNESP] (2022)
Giant unilamellar vesicles (GUVs) are composed of lipophilic layers and are sensitive to the action of reactive oxygen species (ROS). The use of GUVs as microcarriers of biological macromolecules is particularly interesting since ROS produced by gametes or embryos during in vitro culture can induce the opening of pores in the membrane of these vesicles and cause the release of their content. This study investigated the behavior of GUVs [composed of 2-dioleoyl-sn-glycero-3-phosphocholine and 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine-N-(lissamine rhodamine B sulfonyl)] in co-culture with in vitro produced bovine embryos, as well as their embryotoxicity and effectiveness as cysteine carriers in culture medium. Embryonic developmental rates were unaffected, demonstrating the absence of toxicity of GUVs co-cultured with the embryos. No increase of intracellular ROS levels was observed in the embryos co-cultured with GUVs, indicating that the higher lipid content of the culture environment resulting from the lipid composition of the GUV membrane itself did not increase oxidative stress. Variations in the diameter and number of GUVs demonstrated their sensitivity to ROS produced by embryos cultured under conditions that generate oxidative stress. Encapsulation of cysteine in GUVs was found to be more effective in controlling the production of ROS in embryonic cells than direct dilution of this antioxidant in the medium. In conclusion, the use of GUVs in in vitro culture was found to be safe since these vesicles did not promote toxic effects nor did they increase intracellular ROS concentrations in the embryos. GUVs were sensitive to oxidative stress, which resulted in structural changes in response to the action of ROS. The possible slow release of cysteine into the culture medium by GUV rupture would therefore favor the gradual supply of cysteine, prolonging its presence in the medium. Thus, the main implication of the use of GUVs as cysteine microcarriers is the greater effectiveness in preventing the intracytoplasmic increase of ROS in in vitro produced bovine embryos.